IMPACT OF WOUND CARE METHODOLOGY ON PERINEAL HEALING: MODERN VERSUS CONVENTIONAL TREATMENT AT AZ-ZAHRA CLINIC - Farlikhatun, Lili; Pratiwi, Septiyani Nurul (DPW PPNI Provinsi Jawa Barat, 2025)
Introduction: According to the World Health Organization (WHO), approximately 295,000 maternal deaths occurred globally in 2020. Major contributors to maternal mortality include hypertensive disorders of pregnancy (e.g., pre-eclampsia and eclampsia), postpartum hemorrhage, infections, and unsafe abortion (WHO, 2021). Postpartum infections often stem from perineal injuries that fail to heal properly, potentially leading to puerperal sepsis and threatening maternal health (Prawirohardjo, 2018). At the Az-Zahra Clinic in Pebayuran, between November 1 and December 5, 2023, 31 postpartum women with perineal wounds received either modern wound care (58.1%) or conventional care (41.9%). Purpose: This study aimed to examine the association between wound care methods modern versus conventional and the healing of perineal wounds. Methods: A quantitative, cross-sectional design was employed. The study population included all postpartum women with perineal wounds at the Az-Zahra Clinic from November 4 to December 5, 2023, totaling 31 participants. A total sampling technique was used. Results: Statistical analysis yielded a p-value of 0.705 (p > 0.05), indicating no statistically significant relationship between the type of wound care and the healing outcome. The odds ratio (OR) was 0.473 (95% CI: 0.076–2.935), suggesting that modern wound care had a lower, though not statistically significant, likelihood of incomplete healing. Conclusion: Although no significant relationship was found, modern wound care techniques appeared to support faster perineal wound healing. It is recommended that midwives enhance patient education and counseling on perineal wound care, emphasizing hygienic and dry wound management.